Psikologi Kepribadian dalam Perspektif Bimbingan Konseling Islam - Fitriyani, Nina; Rosida, Hilda; Sukirno, Agus; Marina, Selvi; Handayani, Riska (Indonesian Journal of Educational Counseling, 2025)
A more thorough discussion of personality's limiting characteristics is required to fully and completely comprehend human personality. Taking into account biological, social, and cultural aspects, modern psychologists have meticulously examined and tested a wide range of human behaviors. They disregard, however, the study of the human soul and how it affects personality, as well as a thorough comprehension of human personality without comprehending the fundamentals of all the tangible and immaterial components that limit personality. According to the Islamic viewpoint, there are three components to personality dynamics: the base desire (Nafs Al-Ammara Bissu), which is the desire that leads to evil; the controlled desire (Nafs Al-Lawwammah), which is the desire that places blame; and the desire that brings about calm and peace (Nafs Al-Mutma'innah), which is the peaceful desire.